2015
DOI: 10.1103/physrevlett.114.147205
|View full text |Cite
|
Sign up to set email alerts
|

All-In–All-Out Magnetic Domains: X-Ray Diffraction Imaging and Magnetic Field Control

Abstract: Long-range noncollinear all-in-all-out magnetic order has been directly observed for the first time in real space in the pyrochlore Cd_{2}Os_{2}O_{7} using resonant magnetic microdiffraction at the Os L_{3} edge. Two different antiferromagnetic domains related by time-reversal symmetry could be distinguished and have been mapped within the same single crystal. The two types of domains are akin to magnetic twins and were expected-yet unobserved so far-in the all-in-all-out model. Even though the magnetic domain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 34 publications
5
48
0
Order By: Relevance
“…Thus, we think that M rob originates from MDWs; the sample dependence must be due to a difference in the density of crystalline defects that pin down MDWs. The magnitude of M rob is reasonably explained by the observed density of MDWs14 (Supplementary Section 2).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Thus, we think that M rob originates from MDWs; the sample dependence must be due to a difference in the density of crystalline defects that pin down MDWs. The magnitude of M rob is reasonably explained by the observed density of MDWs14 (Supplementary Section 2).…”
Section: Discussionsupporting
confidence: 60%
“…There are two kinds of magnetic domains that can coexist13: the AIAO and all-out/all-in (AOAI) orders related by the time reversal symmetry with each other. The coexistence of the two domains has actually been visualized in Cd 2 Os 2 O 7 by the circular polarized resonant X-ray diffraction imaging technique14. On the other hand, microwave impedance microscopy successfully visualized the MDWs of Nd 2 Ir 2 O 7 , which indicates that the MDWs remain conducting even when the domains themselves become insulating1516.…”
mentioning
confidence: 98%
“…Until its magnetic ground state was revealed, this material was best known as one of a few examples of a Slater insulator [20]. However, recent experimental [19,21] and theoretical [22,23] In this Letter, we report on the detailed temperature (T) evolution of the optical spectra of Cd 2 Os 2 O 7 to reveal how the emergence of AIAO ordering affects the electronic structure and induces the MITs. The absorption edge analyses suggest the Lifshitz-type MIT where a rigid shift of the bands away from the Fermi level E F gradually annihilates the Fermi surface [22,24].…”
mentioning
confidence: 93%
“…Until its magnetic ground state was revealed, this material was best known as one of a few examples of a Slater insulator [20]. However, recent experimental [19,21] and theoretical [22,23] results showed that the magnetic ground state in Cd 2 Os 2 O 7 is AIAO ordering. Investigations on Cd 2 Os 2 O 7 should provide an understanding of how AIAO ordering causes MITs in 5d pyrochlores.…”
mentioning
confidence: 99%
“…An example has been discussed in the peculiar magnetically ordered state called all-in all-out type in pyrochlore oxides. For instance, in Cd 2 Os 2 O 7 , the domain formation was observed using resonant x-ray diffraction, and controllability of the domain structures by a magnetic field-cooling procedure was demonstrated 19 . Meanwhile, for iridium pyrochlore oxides, peculiar electronic states were theoretically predicted, such as the Weyl semimetal 20 and peculiar metallic DWs 21,22 .…”
Section: Introductionmentioning
confidence: 99%